Role of endothelial soluble epoxide hydrolase in cerebrovascular function and ischemic injury. - Wenri Zhang (Public Library of Science (PLoS), 2013)
Soluble Epoxide Hydrolase (sEH) is a key enzyme in the metabolism and termination of action of epoxyeicosatrienoic acids, derivatives of arachidonic acid, which are protective against ischemic stroke. Mice lacking sEH globally are protected from injury following stroke; however, little is known about the role of endothelial sEH in brain ischemia. We generated transgenic mice with endothelial-specific expression of human sEH (Tie2-hsEH), and assessed the effect of transgenic overexpression of endothelial sEH on endothelium-dependent vascular reactivity and ischemic injury following middle cerebral artery occlusion (MCAO). Compared to wild-type, male Tie2-hsEH mice exhibited impaired vasodilation in response to stimulation with 1 µM acetylcholine as assessed by laser-Doppler perfusion monitoring in an in-vivo cranial window preparation. No difference in infarct size was observed between wild-type and Tie2-hsEH male mice. In females, however, Tie2-hsEH mice sustained larger infarcts in striatum, but not cortex, compared to wild-type mice. Sex difference in ischemic injury was maintained in the cortex of Tie2-hsEH mice. In the striatum, expression of Tie2-hsEH resulted in a sex difference, with larger infarct in females than males. These findings demonstrate that transgenic expression of sEH in endothelium results in impaired endothelium-dependent vasodilation in the cerebral circulation, and that females are more susceptible to enhanced ischemic damage as a result of increased endothelial sEH than males, especially in end-arteriolar striatal region.